Does my head look big in this? - Abdel-Fattah, Randa (Scholastic, 2005)
Muslim teenager Amal Abdel-Hakim makes a decision to begin wearing the veil full time. When she does, Amal faces an endless string of teasing and bullying from other students at her preppy suburban high school in Australia.